Analisis Pengaruh Kecepatan Pemotongan dan Kedalaman Pemotongan Terhadap Kekasaran Permukaan Baja SKD11 Dengan Metode RSM - Febriyansa, Agus; Kurniawan, Zaldy; Yudo, Eko (Jurnal Inovasi Teknologi Terapan, 2024)
In the current development of the manufacturing industry, the quality of each product must be met. One machining process, namely CNC lathe, can meet these demands. Surface roughness is one of the values that must be considered again. The minimum surface roughness indicates a very good CNC machining process, because the smaller the surface roughness value of a product, the better the resulting product value. To achieve that all need to du the turning in the right process variables. The process variables that are varied are cutting speed (m/mnt) and depth of cut (mm). Each variable has three levels, mnamely cutting speed 240, 250, and 260. For depth 0,1, 0,15, and 0,2. The research method used to obtain surface roughness values is the response surface methodology (RSM) with a central composite design. The material used in this research is SKD 11 steel. The minimum roughnees is at acutting speed of 240 m/min and a depth of cut of 0,325 mm, the roughness value abtained is an average of 1,627 (µm). for maximum roughness at a cutting speed of 230 m/min and depth of cut of 0,225 mm, the roughness value obtained of 1,975 (µm).